ANALISIS KARAKTERISTIK DAN PEMODELAN KEBUTUHAN PARKIR PADA PUSAT PERBELANJAAN DI KOTA DENPASAR - Sutapa, I Ketut; Suthanaya, Putu Alit; Suweda, I Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008)
Shopping centres in Denpasar are faced with parking supply problems. One of the problems is the difficulty in providing sufficient parking spaces based on actual demand. Efficiency of parking supply can be achieved if parking supply meets actual demand. This research is conducted in order to know parking characteristic, the degree of relation ship between parking demand and parameters of shopping centres as independent variables, to develop parking demand model and to analyse parking demand standard for shopping centres in Denpasar. Primary and secondary data are required in order to know parking characteristics. Primary data were obtained from direct observation onsite which include: parking vehicles data, number of visitor & parking inventory. Primary data were obtained from one day survey an Saturday between 09.00 am to 09.30 pm at each shopping centres. Secondary data (i.e. parameters of shopping centres) were obtained from the management of shopping centres. Shopping centres included in this study are: Robinson, Alfa Imam Bonjol, Ramayana Bali Mall, Tiara Grosir, Alfa Diponegoro and Hardy’s Sesetan. Parking demand models were developed by using simple & multiple regression methods with the help of SPSS 15.0 software. Independent variables included in this study are: floor area, netto floor area, service floor area, number of permanent employees, number of non-permanent employees, number of cashier and number of visitors. The dependent variables are average parking accumulation for car, motor cycle and taxi. Parking demand standards were calculated based on regression analysis of parking demand and shopping centres parameters. The results of the simple regression analysis showed that the relationship between car parking demand and number of non-permanent employees (X5) was indicated by regression formula : Y1 = -1,805 + 0,358.X5 (R2 = 0,965), where the car parking demand standard was 1,097 spaces/person. The relationship between motor cycles parking demand and number of non-permanent employees (X5) was indicated by regression formula: Y2 = -24,497 + 2,059.X5 (R2 = 0,873), where the motor cycles parking demand standard was 6,205 spaces / person. The relationship between taxi parking demand and number of non-permanent employees (X5) was indicated by regression formula: Y3 = -1,262 + 0,037.X5 (R2 = 0,915), where the taxi parking demand standard was 0,001 spaces / person. The results of the multiple regression analysis showed that the relationship between car parking demand and number of non-permanent employees (X5) was indicated by regression formula : Y1 = -1,805 + 0,358.X5 (R2 = 0,965). The relationship between motor cycles parking demand and combination number of permanent employees (X4) with number of non-permanent employees (X5) was indicated by regression formula : Y2 = 135,401 – 1,200.X4 + 2,829 (R2 = 0,972). The relationship between taxi parking demand and number of non-permanent employees (X5) was indicated by regression formula: Y3 = -1,262 + 0,037.X5 (R2 = 0,915).
Keywords: karakteristik parkir, pemodelan parkir, standar kebutuhan parkir